2005
DOI: 10.1002/jsfa.1867
|View full text |Cite
|
Sign up to set email alerts
|

Control of internal browning and quality improvement of ‘Fuji’ apples by stepwise increase of CO2 level during controlled atmosphere storage

Abstract: To control internal browning injury and to reduce quality loss in 'Fuji' apples during storage, a stepwise controlled atmosphere (CA) method was applied in this study. Both non-bagged and bagged apples during maturation were stored at 0 • C under 1% O 2 + 1% CO 2 , 1% O 2 + 3% CO 2 or air for 10 months, and 1% O 2 + 1% CO 2 for 2 months followed by 1% O 2 + 3% CO 2 for 8 months (stepwise CA). The concentrations of internal ethylene and carbon dioxide in apples kept for 24 h at 20 • C after storage under CA con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…They concluded that higher CO 2 levels had an inhibitory eVect on growth and patulin production. Some studies in Fuji apples showed that the loss of Xesh Wrmness, titratable acidity and green color was slower at concentrations of 3% CO 2 than at 1% CO 2 (for 0°C and 1% O 2 ) (Chang, Moon, Chung, & Choi, 2005). This loss of Wrmness and acidity could make fungi grow faster at U-LOW conditions, (with lower percentage of CO 2 ).…”
Section: Discussionmentioning
confidence: 96%
“…They concluded that higher CO 2 levels had an inhibitory eVect on growth and patulin production. Some studies in Fuji apples showed that the loss of Xesh Wrmness, titratable acidity and green color was slower at concentrations of 3% CO 2 than at 1% CO 2 (for 0°C and 1% O 2 ) (Chang, Moon, Chung, & Choi, 2005). This loss of Wrmness and acidity could make fungi grow faster at U-LOW conditions, (with lower percentage of CO 2 ).…”
Section: Discussionmentioning
confidence: 96%
“…Usall et al (2000) and Nunes et al (2002) also reported larger lesion diameters in apples stored during 3 months under U-LO conditions. Chang, Moon, Chung, and Choi (2005) reported that the loss of flesh firmness and titratable acidity in apples is faster at concentrations of 1% of CO 2 than at 3% of CO 2 . This could facilitate the colonization of the fungus.…”
Section: Ca Storage: Effect On Apple Decaymentioning
confidence: 98%
“…The yellowness index (YI) was calculated as follows: 33 YI=Lx*×()bx*||ax*,normalx={}c,1,2,3,4,5,6 where Lx*, ax*, and bx* are the color parameters of the SA gel and FSDN gels.…”
Section: Methodsmentioning
confidence: 99%